The Effect of Work Experience and Working Age on Promotion in The Sijunjung Regency Transportation Office - Lenny Hasan; Henny Sjafitri; Muhammad Ichsan (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to determine how much influence work experience and working age have on promotion for position at the Sijunjung Regency Transportation Office. The research method used is a descriptive quantitative approach . The sampling technique used is non-probability sampling with a saturated sampling method, because the entire population is sampled as many as 88 respondents. The data collection methods used are observation, questionnaires and literature research. The data analysis techniques used are multiple linear regression analysis, t test, F test and coefficient of determination. Based on the results of the t test, the variable of work experience has a positive and significant effect on promotion in the Sijunjung Regency Transportation Office. Meanwhile, the variable of working age has a positive and significant effect on promotion in the Sijunjung Regency Transportation Office. The results of the F test variables of work experience and working age together have a significant effect on promotion in the Sijunjung Regency Transportation Office. While the value of the coefficient of determination is found in the Adjusted R-Square value of 0.247. This means that the ability of the independent variable to explain the dependent variable is 24.7%, the remaining 75.3% is influenced by other variables such as work performance, discipline, education, honesty, loyalty, leadership, cooperation, and so on.